Clinical efficacy of treatment of osteochondrosis with the use of PRP- therapy - I. Yu. Badyin (Kazimierz Wielki University, 2016)
There are a large number of methods for treating patients with cervical osteochondrosis. In the last decade, methods for the use of platelet-rich plasma (PRP) have been actively developed and are being introduced into practical medicine: to favor the engraftment of dental grafts, the healing of chronic trophic fistula of the extremities, and also for the targeted regeneration of damaged organs. The results of treatment of 120 patients with vertebrogenic pathology treated in the neurological department are presented. The obtained data illustrate the improvement of the indices of functional tests of the spine in the group of patients taking PRP-therapy.